Laminin fragments conjugated with perlecan’s growth factor-binding domain differentiate human induced pluripotent stem cells into skin-derived precursor cells - Yoriko Sugiyama-Nakagiri; Shiho Yamashita; Yukimasa Taniguchi; Chisei Shimono; Kiyotoshi Sekiguchi (Scientific Reports, 2023)
Abstract Deriving stem cells to regenerate full-thickness human skin is important for treating skin disorders without invasive surgical procedures. Our previous protocol to differentiate human induced pluripotent stem cells (iPSCs) into skin-derived precursor cells (SKPs) as a source of dermal stem cells employs mouse fibroblasts as feeder cells and is therefore unsuitable for clinical use. Herein, we report a feeder-free method for differentiating iPSCs into SKPs by customising culture substrates. We immunohistochemically screened for laminins expressed in dermal papillae (DP) and explored the conditions for inducing the differentiation of iPSCs into SKPs on recombinant laminin E8 (LM-E8) fragments with or without conjugation to domain I of perlecan (PDI), which binds to growth factors through heparan sulphate chains. Several LM-E8 fragments, including those of LM111, 121, 332, 421, 511, and 521, supported iPSC differentiation into SKPs without PDI conjugation. However, the SKP yield was significantly enhanced on PDI-conjugated LM-E8 fragments. SKPs induced on PDI-conjugated LM111-E8 fragments retained the gene expression patterns characteristic of SKPs, as well as the ability to differentiate into adipocytes, osteocytes, and Schwann cells. Thus, PDI-conjugated LM-E8 fragments are promising agents for inducing iPSC differentiation into SKPs in clinical settings.